2013
DOI: 10.1039/c3ra23295f
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly in surfactant-based mixtures driven by acid–base reactions: bis(2-ethylhexyl) phosphoric acid–n-octylamine systems

Abstract: Structural and dynamic features of bis(2-ethylhexyl) phosphoric acid (HDEHP)-n-octylamine (NOA) mixtures as a function of the NOA mole fraction (X NOA ) have been investigated by SAXS, WAXS, IR, dielectric spectroscopy and polarized optical microscopy. In the 0 ¡ X NOA , 0.5 range, mixtures are transparent liquids, while the abrupt formation of a waxy solid characterized by an hexagonal bidimensional structure occurs at X NOA = 0.5. Such a composition-induced phase transition results from the synergetic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
(30 reference statements)
2
27
0
Order By: Relevance
“…6A) [17,50]. It is interesting to note that the building of unidirectional structures causes an obvious increase in viscosity but also an unexpected reduction of the activation energy of the diffusion and longitudinal relaxation time as reported in the graph of Fig.…”
Section: Amphiphile-based Systems Ii: Mixtures Of Liquid Surfactantsmentioning
confidence: 86%
“…6A) [17,50]. It is interesting to note that the building of unidirectional structures causes an obvious increase in viscosity but also an unexpected reduction of the activation energy of the diffusion and longitudinal relaxation time as reported in the graph of Fig.…”
Section: Amphiphile-based Systems Ii: Mixtures Of Liquid Surfactantsmentioning
confidence: 86%
“…7 Such composition-induced disorder−order transition becomes impressive in the X NOA = 0.5 sample, which appears macroscopically as a waxy solid and, consequently, the 1 H NMR spectrum is characterized by a single very broad signal, centered at 1.85 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is worth noticing that it has been recently found that ionic liquids can be easily prepared by simply mixing two opportunely chosen amphiphilic liquids [18]. In this case, further additional properties can arise, like anysotropical self-assembly [19,20], response to an external magnetic field [21], enhanced proton conductivity [22], and enhanced capability of salt solubilization [23], which can open a wide scenario of new and promising applications.…”
Section: Ionic Liquidsmentioning
confidence: 99%